PEMBINAAN DAN PENGAWASAN LURAH TERHADAP PELAKSANAAN TUGAS RT DAN RW DI KELURAHAN SELENSEN KECAMATAN KEMUNING KABUPATEN INDRAGIRI HILIR TAHUN 2017-2018 - Marlina, Yosi; ", Muchid (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
One that is trusted by the Kelurahan is the government organization that is most directly related to the community. The importance of this guidance is carried out apart from the government requires social institutions in supporting good government development programs, in physical and non physical development. However, it is possible for institutions in the village or kelurahan that issue institutions that actually arise from the community of the village / kelurahan who have just come from outside the village / kelurahan. In addition to cooperating with various institutions in development, another village head's activity is to provide guidance to community institutions in the Kelurahan as one of the tasks of the Lurah in carrying out government tasks. The formulation of the problem in this research is that RT and RW have not optimally carried out their tasks in 2017-2018? And how is the performance of the RT and RW in carrying out their duties in the Selensen district in 2017-2018.This study uses a qualitative approach. Data was collected using primary data and secondary data elements in Kelurahan Selensen, Kemuning Subdistrict, Indragiri Hilir Regency. Data collected through informants in search results. The technique used in data analysis is data reduction in data presentation and drawing conclusions.The results of this study can be stated that, the Role of the Village Head in Developing and Supervising RT and RW in Selensen Village, Kemuning District, Indragiri Hilir Regency has not been implemented optimally, this can be seen from the many planned activities in the field of guidance and supervision carried out by the Village Head to RT and RW and where guidance to the Selensen Kelurahan Community Institution, Kemuning District, However in its implementation most of the planned activities were not realized. the inhibiting factor of the implementation of the Lurah's obligation to foster RT and RW carried out by the lurah to the neighborhood and community units in Selensen Village, Kemuning Subdistrict, Indragiri Hiir Regency. In conclusion, the role of the Lurah in Guiding and Supervising the neighborhood and community units in Selensen Village, Kemuning District, Indragiri Hilir Regency has not been carried out optimally.Keywords: Coaching and Supervision